Optimization of ZnO-NPs to Investigate Their Safe Application by Assessing Their Effect on Soil Nematode Caenorhabditis elegans - Gupta, Shruti (Nanoscale Res Lett, 2015)
Zinc oxide nanoparticles (ZnO-NPs) are increasingly receiving attention due to their widespread application in cosmetics, pigments and coatings. This has raised concerns in the public and scientific communities regarding their unexpected health effects. Toxicity effect of ZnO-NPs on the environment was assessed in the present study using Caenorhabditis elegans. Multiple toxicity end points including their mortality, behaviour, reproduction, in vitro distribution and expression of stress response mtl-1 and sod-1 genes were observed to evaluate safe application of ZnO-NPs. C. elegans were exposed to 10, 50, and 100 nm ZnO-NPs (0.1 to 2.0 g/l). Application of 10 nm ≥0.7g/l adversely affects the survivability of worms and was significantly not affected with exposure of 50 and 100 nm ≤1.0 g/l. However, reproduction was affected at much low concentration as compared to their survivability. LC50 was recorded 1.0 ± 0.06 (g/l) for 100 nm, 0.90 ± 0.60 for 50 nm and 0.620 ± 0.08 for 10 nm. Expression of mtl-1 and sod-1 was significantly increased with application of 10 nm ≥0.7g/l and significantly unaffected with exposure of 50 and 100 nm at the same concentration. ZnO-NPs (10 nm) had shown even distribution extended nearly the entire length of the body. The distribution pattern of ZnO-NPs indicates that the intestine is the major target tissues for NP toxicity. Study demonstrates that small-sized (10 nm) ZnO-NPs ≥0.7g/l is more toxic than larger-sized particles. This may be suggested on the basis of available data; application of 50 and 100 nm ≤1.0 g/l ZnO-NPs may be used to the environment as this shows no significant toxicity. However, further calibration is warranted to explore safe dose on soil compartments prior to their field application.